Enabling High-Performance Computing as a Service. - AbdelBaky, Moustafa; Parashar, Manish; Kim, Hyunjoo; Jordan, Kirk E.; Sachdeva, Vipin; Sexton, James; Jamjoom, Hani; Shae, Zon-Yin; Pencheva, Gergina; Tavakoli, Reza; Wheeler, Mary F. (Computer (00189162), 2012)
With the right software infrastructure, clouds can provide scientists with "as a service" access to high-performance computing resources. An award-winning prototype framework transforms the Blue Gene/P system into an elastic cloud to run a representative HPC application. The Web extra at http://youtu.be/TidQezFUK0E is a video demonstrating an award-winning prototype framework that transforms the Blue Gene/P system into an elastic cloud to run a representative high-performance computing application.